Aminoglycoside sulfate modified aqueous battery electrolyte as well as preparation method and application thereof
By using aminoglycoside sulfates as electrolyte additives in aqueous zinc metal batteries, the solvation structure of zinc ions and the construction of a water-poor interface protective layer is solved, and the problem of uneven deposition and self-corrosion of zinc metal batteries during circulation is solved. , significantly improves the cycle stability and performance of the battery.
Patent Information
- Application Number
- CN202411251853.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-30
- Filing Date
- 2024-09-06
- Publication Date
- 2025-01-14
AI Technical Summary
During the charge and discharge cycle, zinc is preferred for zinc deposition due to the non-uniform interface of zinc metal, which reduces cycle life and Coulomb efficiency, and is prone to self-corrosion and electrochemical corrosion, affecting the stable electrochemical cycle.
Using aminoglycoside sulfates as the modification additive of the electrolyte, by destroying the hydrogen bond network in the solution, limiting the activity of water, changing the solvation structure of zinc ions, inducing uniform deposition of zinc, and building a water-poor interface protective layer to inhibit Side reaction of zinc metal negative electrode.
It significantly improves the cycle stability and rate performance of zinc ion secondary batteries. The cycle life of zinc symmetrical batteries can reach more than 3300 hours. The cycle capacity retention rate of zinc metal batteries can reach more than 95% under high current conditions, meeting the performance of power batteries. Require.
Smart Images

Figure CN119315127A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a modified aqueous zinc metal battery electrolyte, in particular to an aminoglycoside sulfate modified aqueous battery electrolyte and a preparation method and application thereof, and belongs to the field of electrochemical energy storage and new energy materials. Background Art
[0002] With the rapid development of modern society, people have gradually realized the continuous deterioration of the natural environment and the continued intensification of the energy crisis. Therefore, people have begun to focus on exploring the use of renewable energy. Among them, as an important energy storage device, the development and application of rechargeable batteries is an inevitable trend to cope with the growing energy consumption and climate and environmental problems. Since its commercialization in the 1990s, lithium-ion batteries have been widely used in various fields such as life, national defense, and production, such as electric vehicles, portable electronic devices, etc. due to their high energy density and long cycle life. However, the cost of lithium-ion batteries has remained high, and more importantly, the safety cannot be fundamentally guaranteed, so it has always been limited in large-scale energy storage applications. In order to completely solve the two major problems of lithium-ion batteries, it is urgent to develop a new energy storage system that is both low-cost and highly safe.
[0003] Aqueous zinc metal batteries have gradually attracted widespread attention from researchers due to their advantages and are considered to be a new generation of safe energy storage systems. (1) Low cost and high safety: The use of cheap zinc metal and aqueous solution can greatly reduce the cost of material production. In addition, the high chemical stability of zinc and water further reduces the equipment assembly budget and improves manufacturing safety and life cycle; (2) Good performance: It has a higher conductivity than organic electrolytes (~0.1S cm -1 )Higher ionic conductivity (<10mScm -1 ), resulting in excellent rate performance and using a high theoretical capacity (820mAh g -1 ) Zinc metal can achieve higher energy density; (3) Protect the environment and save resources: Replacing organic electrolytes with water can significantly reduce pollution levels, and the smelting, processing and recycling of zinc are more mature than lithium, which is conducive to protecting the environment and saving resources.
[0004] However, zinc metal batteries still have the following problems, which hinder their further commercial application. (1) During the charge and discharge cycle, the strong ion transport current generated by the "tip effect" of the zinc metal heterogeneous interface will lead to the preferential deposition of zinc, thereby reducing the cycle life and coulombic efficiency; (2) From a thermodynamic point of view, compared with zinc deposition, hydrogen evolution is more likely to occur, and hydrogen evolution further causes a local alkaline environment at the solid-liquid interface, resulting in the formation of by-products; (3) Self-corrosion and electrochemical corrosion will occur, destroying the stable electrochemical cycle.
[0005] In response to the above problems, the negative electrode protection strategies of aqueous zinc metal batteries can be mainly divided into the following three types: solid-liquid interface regulation, zinc negative electrode structure design and electrolyte modification. The electrolyte modification strategies specifically include additives, co-solvents, high-concentration electrolytes, and deep eutectic solvent electrolytes. Among them, electrolyte additives, that is, regulating the electrolyte environment through a small amount of additives to optimize the deposition behavior of zinc ions, have a "four-two-pound" effect. In practice, electrolyte additives have become the most commonly used optimization strategy because the method is simple, easy to implement and compatible with existing battery manufacturing methods.
[0006] At present, there are two main types of electrolyte additives used in aqueous zinc metal batteries: one is metal ion additives, including Na + Mg 2+ 、Co 2+ , Mn 2+ 、Al 3+ etc.; the second is organic additives, which are the most diverse, including organic acids, polymers, surfactants, etc. Organic additives can not only protect the zinc negative electrode and induce uniform zinc deposition, but also regulate the electrolyte environment and change the zinc ion solvation structure, so that zinc metal batteries can be cycled stably for a long time. Therefore, safe, effective and low-cost organic additives have gradually become a research hotspot, and the cycling performance under more stringent current density conditions needs to be further explored. Summary of the invention
[0007] In view of the problems existing in the prior art, the first object of the present invention is to provide an aqueous battery electrolyte modified by aminoglycoside sulfate. The battery electrolyte uses aminoglycoside sulfate as a modifier, which destroys the hydrogen bond network in the solution, limits the activity of water, changes the solvation structure of zinc ions, and induces uniform zinc deposition on the surface of the zinc metal negative electrode, and constructs a water-poor interface protective layer, thereby greatly inhibiting the occurrence of side reactions of the zinc metal negative electrode.
[0008] The second object of the present invention is to provide a method for preparing an aqueous battery electrolyte modified by aminoglycoside sulfate. The method adopts a liquid phase reaction and can prepare the electrolyte only by stirring and dissolving. The method has the advantages of simple process, low equipment requirements, wide sources of raw materials and low cost, and can meet the requirements of large-scale industrial production.
[0009] The third object of the present invention is to provide an application of an aqueous battery electrolyte modified by aminoglycoside sulfate to prepare an aqueous zinc metal secondary battery. Based on the beneficial technical effects of the above battery electrolyte, it is applied to a zinc ion secondary battery to effectively improve the cycle stability and rate performance of the battery. After testing, the zinc ion secondary battery prepared by the electrolyte provided by the present invention has a cycle life of more than 3300h for a zinc symmetrical battery and a cycle life of more than 3300h for a zinc metal full battery at 5Ag. -1Under high current conditions, the cycle capacity retention rate can reach more than 95%, which can meet the performance requirements of power batteries.
[0010] In order to achieve the above technical objectives, the present invention provides an aminoglycoside sulfate-modified aqueous battery electrolyte, comprising a zinc ion solution and a modifying additive; the modifying additive is an aminoglycoside sulfate, and its concentration in the electrolyte is 0.001 to 0.1 mol / L; the zinc ion concentration in the electrolyte is 1 to 4 mol / L.
[0011] As a preferred solution, the concentration of the modifying additive in the electrolyte is 0.035-0.045 mol / L.
[0012] As a preferred solution, the zinc ion concentration in the electrolyte is 1.9 to 3.1 mol / L.
[0013] As a preferred solution, the zinc ions in the electrolyte are provided by soluble inorganic and / or organic zinc salts.
[0014] As a preferred embodiment, the aminoglycoside sulfate is at least one of amikacin sulfate, gentamicin sulfate and neomycin sulfate.
[0015] As a preferred solution, the source of zinc ions in the electrolyte is at least one of ZnSO4, Zn(CF3SO3)2, and ZnCl2.
[0016] As a preferred embodiment, the aminoglycoside sulfate is amikacin sulfate.
[0017] As a preferred solution, when the source of zinc ions in the electrolyte is ZnSO4, the concentration of zinc ions is 1.95-2.05 mol / L.
[0018] As a preferred solution, when the source of zinc ions in the electrolyte is Zn(CF3SO3)2, the concentration of zinc ions is 2.95-3.05 mol / L.
[0019] The present invention also provides a method for preparing an aminoglycoside sulfate-modified aqueous battery electrolyte, which is obtained by fully mixing and dissolving raw materials including a zinc ion solution and a modified additive.
[0020] The present invention also provides an application of an aminoglycoside sulfate-modified aqueous battery electrolyte for preparing an aqueous zinc metal secondary battery; the secondary battery comprises a battery positive electrode, a battery negative electrode, a separator and the battery electrolyte according to any one of claims 1 to 5.
[0021] As a preferred solution, the positive electrode is at least one of zinc metal, vanadium-based oxides, manganese-based oxides, Prussian blue analogs and organic materials.
[0022] As a preferred solution, the negative electrode is zinc metal.
[0023] As a preferred solution, the vanadium-based oxide is V2O5, V x O y 、M x V y O z Vanadate, V x O y nH2O and M x V y O z One of H2O.
[0024] As a preferred embodiment, the manganese-based oxide is one of α-MnO2, β-MnO2, δ-MnO2 and ZnMn2O4.
[0025] As a preferred embodiment, the Prussian blue analogs are PBAs, ZnHCF, CuHCF and CoFe(CN)6.
[0026] As a preferred solution, the organic material is one of PANI, PANI / CFs, PANI-GO / CNTs, PANI-CNTs-PEDOT, PANI-CNTs-TPU, CC-PANI-FeCN, PANI / Graphene, PANI / Carbon Fiber and PANI / Cellulose Papers.
[0027] As a preferred solution, the diaphragm is at least one of a glass fiber membrane, a single-layer PP membrane, a single-layer PE membrane, a PP+ceramic coating membrane, a PE+ceramic coating membrane, a double-layer PP / PE membrane, a double-layer PP / PP and a three-layer PP / PE / PP membrane, a Nafion membrane, a PVDF membrane, a porous polymer membrane, a non-woven fabric diaphragm and an inorganic composite membrane.
[0028] Compared with the prior art solutions, the beneficial technical solutions of the technical solution of the present invention are:
[0029] 1) The battery electrolyte provided by the present invention uses aminoglycoside sulfate as a modifier, which destroys the hydrogen bond network in the solution, limits the activity of water, changes the solvation structure of zinc ions, and induces uniform zinc deposition on the surface of the zinc metal negative electrode, and constructs a water-poor interface protective layer, thereby greatly inhibiting the occurrence of side reactions of the zinc metal negative electrode;
[0030] 2) The preparation method provided by the present invention adopts a liquid phase reaction, and the preparation of the electrolyte can be achieved only by stirring and dissolving. The method has the advantages of simple process, low equipment requirements, wide sources of raw materials and low cost, and can meet the requirements of large-scale industrial production;
[0031] 3) In the technical solution provided by the present invention, based on the beneficial technical effects of the above-mentioned battery electrolyte, it is applied to zinc ion secondary batteries, which can effectively improve the cycle stability and rate performance of the battery. After testing, the zinc ion secondary battery prepared by the electrolyte provided by the present invention has a cycle life of more than 3300h for the zinc symmetrical battery and a cycle life of more than 3300h for the zinc metal full battery at 5Ag. -1 Under high current conditions, the cycle capacity retention rate can reach more than 95%, which can meet the performance requirements of power batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a test diagram of the cycle life of zinc symmetric batteries of comparative example 1 and examples 1 to 5;
[0033] Figure 2 This is the zinc negative electrode deposition morphology;
[0034] in Figure 2 (a) is the zinc deposition morphology of comparative example 1; Figure 2 (b) is the zinc deposition morphology of Example 3;
[0035] Figure 3 XRD diagram of the Zn negative electrode after cycling in Comparative Example 1 and Example 3;
[0036] Figure 4 It is a test diagram of the cycle life of the zinc symmetric battery of Comparative Example 2 and Example 6;
[0037] Figure 5 1 is a charge-discharge cycle diagram of the Zn||NaVO full battery of Comparative Example 3 and Example 7;
[0038] Figure 6 It is a test diagram of the cycle life of the zinc symmetric battery of Comparative Example 1 and Example 8;
[0039] Figure 7 It is a test diagram of the cycle life of the zinc symmetric battery of Comparative Example 2 and Example 9;
[0040] Figure 8 1 is a charge-discharge cycle diagram of the Zn||NaVO full battery of Comparative Example 3 and Example 10;
[0041] Fig. 9 It is a test diagram of the cycle life of the zinc symmetric battery of Comparative Example 1 and Example 11;
[0042] Fig.10It is a test diagram of the cycle life of the zinc symmetric battery of Comparative Example 2 and Example 12;
[0043] Fig.11 1 is the charge and discharge cycle diagram of the Zn||NaVO full battery of Comparative Example 3 and Example 13. DETAILED DESCRIPTION
[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can also be obtained based on these drawings without creative work. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0045] The present invention adopts amikacin sulfate (AS) and the like as an aqueous zinc metal battery additive, and can achieve a long-term cycle of the zinc metal battery.
[0046] In the present invention, the conditions for testing the cycle life of the battery are:
[0047] The Zn||Zn symmetrical battery and Zn||NaVO full battery prepared in the following comparative example were subjected to charge and discharge cycle tests using the Xinwei battery testing system.
[0048] The experimental conditions for constant temperature charge and discharge are as follows: the products of the comparative example and the embodiment are tested in a symmetrical battery at 30°C, and the current density of the Zn||Zn symmetrical battery during charge and discharge is 1 mA cm -2 ; Charging time and discharging time are both 1h; Zn||NaVO full battery at 0.1Ag -1 After 2 cycles of activation under current, 5Ag -1 High current charge and discharge cycles.
[0049] The preparation process of the battery electrolyte used in the embodiment of the present invention is: fully dissolving zinc salt in deionized water to obtain a zinc ion solution, and then adding aminoglycoside sulfate to fully dissolve to obtain the electrolyte.
[0050] Example 1
[0051] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.001 mol / L amikacin sulfate (AS). The battery is named ZS+0.001MASZn||Zn.
[0052] Example 2
[0053] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.02 mol / L amikacin sulfate (AS). The battery is named ZS+0.02MASZn||Zn.
[0054] Example 3
[0055] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.04 mol / L amikacin sulfate (AS). The battery is named ZS+0.04MASZn||Zn.
[0056] Example 4
[0057] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.06 mol / L amikacin sulfate (AS). The battery is named ZS+0.06MASZn||Zn.
[0058] Example 5
[0059] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.1 mol / L amikacin sulfate (AS). The battery is named ZS+0.1MASZn||Zn.
[0060] Example 6
[0061] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 3 mol / L Zn(CF3SO3)2 and 0.04 mol / L amikacin sulfate (AS). The battery is named ZF+0.04MASZn||Zn.
[0062] Example 7
[0063] This embodiment provides a Zn||NaVO full battery, with zinc metal as the negative electrode, glass fiber as the separator, NaVO as the positive electrode, and the electrolyte being an aqueous solution of 3 mol / L Zn(CF3SO3)2 and 0.04 mol / L amikacin sulfate (AS). The battery is named ZF+0.04MASZn||NaVO.
[0064] Example 8
[0065] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.04 mol / L gentamicin sulfate (GS). The battery is named ZS+0.04MGSZn||Zn.
[0066] Example 9
[0067] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 3 mol / L Zn(CF3SO3)2 and 0.04 mol / L gentamicin sulfate (GS). The battery is named ZF+0.04MGSZn||Zn.
[0068] Example 10
[0069] This embodiment provides a Zn||NaVO full battery, with zinc metal as the negative electrode, glass fiber as the separator, NaVO as the positive electrode, and the electrolyte being an aqueous solution of 3 mol / L Zn(CF3SO3)2 and 0.04 mol / L gentamicin sulfate (GS). The battery is named ZF+0.04MGSZn||NaVO.
[0070] Embodiment 11
[0071] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 2 mol / L ZnSO4 and 0.04 mol / L neomycin sulfate (NS). The battery is named ZS+0.04MNSZn||Zn.
[0072] Example 12
[0073] This embodiment provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being an aqueous solution of 3 mol / L Zn(CF3SO3)2 and 0.04 mol / L neomycin sulfate (NS). The battery is named ZF+0.04MNSZn||Zn.
[0074] Embodiment 13
[0075] This embodiment provides a Zn||NaVO full battery, with zinc metal as the negative electrode, glass fiber as the separator, NaVO as the positive electrode, and the electrolyte being an aqueous solution of 3 mol / L Zn(CF3SO3)2 and 0.04 mol / L neomycin sulfate (NS). The battery is named ZF+0.04MNSZn||NaVO.
[0076] Comparative Example 1
[0077] This comparative example provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being a 2 mol / L ZnSO4 aqueous solution. The battery is named ZSZn||Zn.
[0078] Comparative Example 2
[0079] This comparative example provides a Zn||Zn symmetrical battery, with zinc metal as the negative electrode, glass fiber as the separator, zinc metal as the positive electrode, and the electrolyte being a 3 mol / L Zn(CF3SO3)2 aqueous solution. The battery is named ZFZn||Zn.
[0080] Comparative Example 3
[0081] This embodiment provides a Zn||NaVO full battery, with zinc metal as the negative electrode, glass fiber as the separator, NaVO as the positive electrode, and the electrolyte being a 3 mol / L Zn(CF3SO3)2 aqueous solution. The battery is named ZFZn||NaVO.
[0082] The Zn||Zn symmetrical battery 1 mA cm -2 The charge and discharge cycles are compared in groups, such as Figure 1 The battery cycle life of comparative example 1 is about 120 hours, while the cycle life of example 1 reaches about 950 hours, the cycle life of example 2 reaches about 2900 hours, the cycle life of example 3 reaches about 3300 hours, the cycle life of example 4 reaches about 1850 hours, and the cycle life of example 5 reaches about 1600 hours.
[0083] Comparative Example 1 and Example 3 were cycled for 50 cycles at the same time, the batteries were disassembled, the morphology of the zinc negative electrode was observed by scanning electron microscopy, and the formation of by-products was detected by XRD. Figure 2 , 3 As shown. By comparison, it can be found that after 50 cycles in the electrolyte without additives, Figure 2 (a) The zinc deposition on the surface of the zinc negative electrode shows an uneven growth trend, and the surface roughness is too high, indicating that zinc dendrites can easily pierce the diaphragm and cause battery short circuit, which also corresponds to the problem of short cycle life of symmetrical batteries; after 50 cycles in the electrolyte with additives, such as Figure 2 (b), the zinc deposition on the surface of the zinc negative electrode is uniform and flat. Figure 3 After 50 cycles in the electrolyte without additives, an obvious by-product peak appeared on the zinc negative electrode; after 50 cycles in the electrolyte with additives, the by-products on the surface of the zinc negative electrode were significantly reduced.
[0084] The charge and discharge cycles of the Zn||Zn symmetric battery of the above comparative example 2 and embodiment 6 are compared in a group diagram, as shown in FIG. Figure 4 The battery cycle life of Comparative Example 2 is about 80 hours, while the cycle life of Example 6 reaches about 2950 hours. Different electrolyte systems are equally effective, which reflects the universal applicability of the amikacin sulfate (AS) additive.
[0085] The Zn||NaVO full battery charge and discharge cycles of the above-mentioned comparative example 3 and embodiment 7 are compared in a group diagram, as shown in FIG. Figure 5 As shown. In 5Ag -1 Under the condition of high current, the capacity retention rate of the battery of comparative example 3 after 3000 cycles is only 46.52%, while the capacity retention rate of the battery obtained in example 7 after 3000 cycles is 95.92%. The addition of additives greatly improves the cycle stability of the zinc metal full battery and extends the service life of the full battery.
[0086] The charge and discharge cycles of the Zn||Zn symmetric battery of the above comparative example 1 and embodiments 8 and 11 are compared in a group diagram. Figure 6 , 9 The battery cycle life of Comparative Example 1 is about 120 hours, while the cycle life of Example 8 reaches about 3200 hours, and the cycle life of Example 11 also reaches more than 1300 hours. Different additives are equally effective in the zinc sulfate system, which reflects the universal applicability of aminoglycoside sulfate additives in the zinc sulfate system.
[0087] The charge and discharge cycles of the Zn||Zn symmetric battery of the above comparative example 2 and examples 9 and 12 are compared in a group diagram. Figure 7 , 10 The battery cycle life of Comparative Example 1 is about 80 hours, while the cycle life of Examples 9 and 12 reaches more than 2600 hours. Different additives are equally effective in the zinc sulfonate system, which shows that aminoglycoside sulfate additives also generally have an improvement effect in the zinc sulfonate system.
[0088] The Zn||NaVO full battery charge and discharge cycles of the above comparative example 3 and examples 10 and 13 are compared in a group diagram. Figure 8 , 11 As shown. In 5Ag -1 Under the condition of high current, the capacity retention rate of the battery of Comparative Example 3 after 3000 cycles is only 46.52%, while the capacity retention rate of the battery obtained in Example 10 after 3000 cycles is 82.27%, and the capacity retention rate of the battery obtained in Example 13 after 4000 cycles is 88.58%, indicating that the addition of different aminoglycoside sulfate additives can improve the cycle stability of the zinc metal full battery and extend the service life of the full battery.
Claims
1. Aminoglycoside sulfate-modified aqueous battery electrolyte, characterized in that: The invention comprises a zinc ion solution and a modification additive; the modification additive is an aminoglycoside sulfate, and the concentration of the aminoglycoside sulfate in the electrolyte is 0.001-0.1 mol / L; and the zinc ion concentration in the electrolyte is 1-4 mol / L.
2. The aminoglycoside sulfate-modified aqueous battery electrolyte according to claim 1, characterized in that: The concentration of the modified additive in the electrolyte is 0.035-0.045 mol / L; the concentration of zinc ions in the electrolyte is 1.9-3.1 mol / L.
3. The aminoglycoside sulfate-modified aqueous battery electrolyte according to claim 1, characterized in that: The zinc ions in the electrolyte are provided by soluble inorganic and / or organic zinc salts; the aminoglycoside sulfate is at least one of amikacin sulfate, gentamicin sulfate and neomycin sulfate.
4. The aminoglycoside sulfate-modified aqueous battery electrolyte according to claim 3, characterized in that: The source of zinc ions in the electrolyte is at least one of ZnSO4, Zn(CF3SO3)2, and ZnCl2; and the aminoglycoside sulfate is amikacin sulfate.
5. The aminoglycoside sulfate-modified aqueous battery electrolyte according to claim 4, characterized in that: When the zinc ion source in the electrolyte is ZnSO4, the concentration of zinc ions is 1.95-2.05 mol / L; when the zinc ion source in the electrolyte is Zn(CF3SO3)2, the concentration of zinc ions is 2.95-3.05 mol / L.
6. The method for preparing the aminoglycoside sulfate-modified aqueous battery electrolyte according to any one of claims 1 to 5, characterized in that: The raw materials including the zinc ion solution and the modified additive are fully mixed and dissolved to obtain the product.
7. The use of the aminoglycoside sulfate modified aqueous battery electrolyte according to any one of claims 1 to 5, characterized in that: Used to prepare an aqueous zinc metal secondary battery; the secondary battery comprises a battery positive electrode, a battery negative electrode, a separator and a battery electrolyte as described in any one of claims 1 to 5.
8. The use of the aminoglycoside sulfate modified aqueous battery electrolyte according to claim 7, characterized in that: The positive electrode is at least one of zinc metal, vanadium-based oxides, manganese-based oxides, Prussian blue analogs and organic materials; the negative electrode is zinc metal.
9. The use of the aminoglycoside sulfate modified aqueous battery electrolyte according to claim 8, characterized in that: The vanadium-based oxide is V2O5, V x O y 、M x V y O z Vanadate, V x O y nH2O and M x V y O z ·H2O; the manganese-based oxide is one of α-MnO2, β-MnO2, δ-MnO2 and ZnMn2O4; the Prussian blue analogue is PBAs, ZnHCF, CuHCF and CoFe(CN)6; the organic material is one of PANI, PANI / CFs, PANI-GO / CNTs, PANI-CNTs-PEDOT, PANI-CNTs-TPU, CC-PANI-FeCN, PANI / Graphene, PANI / Carbon Fiber and PANI / CellulosePapers.
10. The use of the aminoglycoside sulfate modified aqueous battery electrolyte according to claim 7, characterized in that: The diaphragm is at least one of a glass fiber membrane, a single-layer PP membrane, a single-layer PE membrane, a PP+ceramic coating membrane, a PE+ceramic coating membrane, a double-layer PP / PE membrane, a double-layer PP / PP and a triple-layer PP / PE / PP membrane, a Nafion membrane, a PVDF membrane, a porous polymer membrane, a non-woven fabric diaphragm and an inorganic composite membrane.
Citation Information
Patent Citations
Aqueous zinc ion battery electrolyte of small organic molecule additive containing amino and hydroxyl as well as preparation method and application of aqueous zinc ion battery electrolyte
CN116565347A
Application of benzoquinone micromolecules as additive in preparation of electrolyte
CN117292952A
Methods of treating acne and rosacea with primary battery generated electricity
CN1826153A
Device for treatment of barrier membranes
US20040267169A1